Boundedness of One-Sided Oscillatory Integral Operators on Weighted Lebesgue Spaces. (3rd February 2014) - Fu, Zunwei; Lu, Shanzhen; Pan, Yibiao; Shi, Shaoguang
Abstract : We consider one-sided weight classes of Muckenhoupt type, but larger than the classical Muckenhoupt classes, and study the boundedness of one-sided oscillatory integral operators on weighted Lebesgue spaces using interpolation of operators with change of measures.